Money as an indicator variable for monetary policy when money demand is forward looking - Lauri Kajanoja (Bank of Finland, 2003)
This paper studies the gain from using money as an indicator when monetary policy in made under data uncertainty.We use a forward and backward looking model, calibrated for the euro area.The policymaker cannot completely observe the state of the economy. Money reveals some of the private sector's information to the policymaker, especially if there is a forward looking element in money demand.We show that observing money can considerably reduce the loss that is due to incomplete information.However, taking also into account other financial market data could decrease the marginal importance of money as an indicator.
URN:NBN:fi:bof-20140807475
Keywords: E52; E58; E47; 330; monetary policy; partial information; money; monetary aggregates; euro area